(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article analyzes the hypernymy and hyponymy relations of psychological lexical units in the English and Uzbek languages. These relations are not only essential in most fields, but also particularly in psychology. By these relations, several psychological lexical units can be grouped and classified, making them efficient to analyze. Examples in both languages are presented producing contrastive analysis.